THE INFLUENCE OF FINANCIAL DISTRESS, GOING CONCERN OPINION, PROFITABILITY, MANAGEMENT CHANGES, AND COMPANY GROWTH ON AUDITOR SWITCHING - Suyatni Utami; Rusmawan Wahyu Anggoro (Jurnal Ekonomi Dan Bisnis, 2023)
This study aims to determine whether there is an effect offinancial distress, going concern opinion, profitability, management changes, and company growth on auditor switching ofproperty and real estate sector companies listed on the Indonesia Stock Exchange from 2014 to 2020. Purposive sampling was usedto select the sample, 79 companies were selected and 24 met the criteria.The selected samplewas tested (24 companies or 168 observations)and analyzedusingLogistic Regression Analysis(LRA) techniques.The results indicatethat financial distress and profitability have no effecton voluntary auditor switching whilegoing concern opinion,company growth,and management changesinfluencedvoluntary auditor switching.Based on this research limitation, further research shoulduse another sector, addingnewvariables and usingbetter techniquesfor detecting auditor switchingto increase the power of the tests.